STUDI LITERATUR: DETERMINAN KECURANGAN LAPORAN KEUANGAN - Setyowati, Widya Arum; Risma, Chesylia Ayu; Nugrahanti, Trinandari Prasetya (Jurnal Akuntansi, 2025)
This study aims to analyze the determinants of financial statement fraud from the perspective of Agency Theory and Fraud Theory, including Fraud Hexagon Theory, Fraud Pentagon Theory, and Fraud Star Theory. The literature review method was employed using the Systematic Literature Review (SLR) method. Secondary data were collected from 18 scholarly articles published on Google Scholar between 2020 and 2025. The findings of this study indicate that factors such as pressure, opportunity, rationalization, capability or competence, ego or arrogance, collusion, and lack of integrity are factors that influence the occurrence of financial statement fraud.